"دور الذكاء الاقتصادي في تعزيز تنافسية المؤسسات الاقتصادية الجزائرية دراسة حالة عينة من المؤسسات الاقتصادية بالولاية المنتدبة تقرت " - الزهرة, مداني; نادية, النيبوع; ايناس, بن جدة (University of eloued جامعة الوادي, 2020)
تهدف هذه الدراسة إلى التعرف على دور الذكاء الاقتصادي في تعزيز تنافسية المؤسسة الاقتصادية، إذ أن الذكاء الاقتصادي يعد أحد الخيارات الضرورية أمام المؤسسة الاقتصادية لتعزيز تنافسيها وضمان بقاءها و إستمراريتها، ويتم تحديد الدور من خلال دراسة علاقة الارتباط بين أبعاد الذكاء الاقتصادي والتنافسية، لذلك أجريت الدراسة على عينة من المؤسسات الاقتصادية بالولاية المنتدبة تقرت حيث تم الاعتماد على أسلوبين متكاملين، الأول وصفي بالاستناد على عدد من الأدبيات لتوضيح الخلفية النظرية للذكاء الاقتصادي وتنافسية المؤسسة الاقتصادية، أما الأسلوب الثاني فهو الأسلوب التحليلي بتطبيق دراسة استكشافية من خلال الاستبيان كأداة لجمع البيانات، إذ تم توزيع 30 استبانه على مسؤولي المصالح وعدد من الموظفين وتم تحليل البيانات باستخدام برنامج Spss و أدوات إحصائية، وتوصلت الدراسة إلى وجود علاقة ذات دلالة إحصائية بين الذكاء الاقتصادي وتعزيز تنافسية المؤسسات الاقتصادية محل الدراسة، وخلصت إلى تقديم اقتراحات من أهمها ضرورة توسيع دائرة استخدام الذكاء الاقتصادي."This research aims to identify and reinforce the role of economic intelligence in the competitiveness of the economic institution. In order to enhance its competitiveness, to secure its survival and its continuity, the economic intelligence is highly necessary in the economic institution. The role of economic intelligence is determined by the study of correlation between the interval of the economic intelligence and its competitiveness. Thus, a study has been conducted on a sample of the economic institutions in the State of TOUGGOURT, where two complementary methods has been relied on:The first one was a descriptive one where, it was based on literature to clarify the theoretical background of the economic intelligence and, the competitiveness of the economic institution. While, the second one was analytic” CING” dependent on the application of an exploratory study through a questionnaire as a tool to gather the data. Thirty questionnaires has been distributedon the responsible of the interests and a group of employees where, data has been analyzed by using the “Spss” program and statistics tools.As a result, this research has found a statistic relevant relationship between the economic intelligence and the competitiveness in economic institutions.As a conclusion, this research provides important suggestions among them: Expanding the use of economic intelligence. "
مذكرة ماستر اقتصاد وتسيير نؤسسات
Keywords: الذكاء الاقتصادي، التنافسية، اليقظة الإستراتيجية، الحماية والأمن، الضغط و التأثير.; economic intelligence, competitiveness, vigilance strategy, security and protection, pressure and impact.